Gross Adaptive Morphologic Changes Occurring in the Gastrointestinal Tract Components of Ostriches Fed Ration Including or Excluding Grit in Botswana - Waugh, E.E.; Dzoma, B.M.; Seabo, D.; Aganga, A.A.; Tsopito, C.M.; Omphile, U.J.; Sebolai, B.; Malela, L. (International Journal of Poultry Science, 2007)
This study investigated the gross changes occurring in the luminal surface and structural anatomy of some Gastrointestinal Tract (GIT) components of ostriches with access to grit and of ostriches without access to grit. Fourteen ostrich chicks age ten weeks were raised on concrete without access to grit were randomly assigned to two feeding groups. Each feeding group had seven birds raised in a pen 30 meters long by 6 meters wide. All ostriches were fed and watered ad libitum. One group had access to grit through out the study while the other group did not have access to grits. From week 24 an ostrich from each group was slaughtered monthly. Gastrointestinal components were dissected and weights with and without contents recorded. The length of tubular components was measured. Digital photographs were taken of the external morphology and of the luminal surfaces of proventriculus and ventriculus (gizzard). Measurements were taken of the height of proventricular mucosal folds and the thickness of the ventricular muscle. The volume of the proventriculus and of the ventriculus was determined by measuring the volume of water displaced by the organs. The data was analyzed using the student-t test at p<0.05. The proventricular mucosal folds of the grit group were significantly lower (0.49±0.09 cm) than the proventricular mucosal folds (1.06±0.09 cm) of the no grit group. This change in the mucosal fold does alter surface area of the proventricular mucosa in contact with ingester and could therefore positively affect digestion in the no grit group. There was no significant difference between percent body weight (0.85±0.07) of and the volume of water displaced (810.71±62.01 mL) by the proventriculus of the no grit group and percent body weight (0.94±0.07) and volume of water displaced (692.43±62.01 mL) by the proventriculus of the grit group. Ventricular percent body weight (0.96±0.07) of the no grit group and percent body weight (1.12±0.07) of the grit group were not significantly different. However there was a significant difference between the volume of water displaced (817.14±40.47 mL) by the ventriculus of the no grit group and the volume displaced (1045.86±40.47 mL) by the ventriculus of the grit group. There was similarly a significant difference between the muscle thickness (4.88±0.23 cm) of the ventriculus of the no grit group and the muscle thickness (6.27±0.23 cm) of the ventriculus of the grit group. Digital photography revealed more eroded luminal folds of both proventriculus and ventriculus of the grit group compared to those of the no grit group. The stark contrast in size of the ventriculus of the two treatment groups of birds was also demonstrated with digital photography. There was no significant difference between the percent body weight (0.98±0.03) and length (611.14±30.30 cm) of the small intestines of the no grit group and the percent body weight (1.01±0.03) and the length (704.14±30.30 cm) of the small intestines of the grit group. No significant difference was found between percent body wt (0.23±0.01) of the caecum of the no grit group and the percent body weight (0.20±0.01) of that of the grit group. However the caecal length (70.42±1.67 cm) of the no grit group was significantly different from the caecal length (82.28±1.67 cm) of the grit group. The percent body weight (1.27±0.05) and the length (938.57±51.11 cm) of the large intestines for the no grit group was not significantly different from the percent body weight (1.34±0.05) and the length (941.17±51.11 cm) of the large intestines for the grit group. Access to grits lead to a significant hypertrophy of the tunica muscularis of the gizzard and should thus increase the grinding power of the organ and its digestive efficiency. The significant erosion of the proventricular mucosal folds in birds with access to grit compared to the proventricular mucosal folds of the no grit group is likely to reduce digestive efficiency of this organ in the grit group of ostriches. The presence of grits had no significant impact on the parameters examined for the large and small intestines. This is in contrast to the caecum, which showed a significant increase in length in the birds exposed to grits.